Inter-Religious Harmony: From History to Indonesia Today - Noor Achmad (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Indonesia is an incredibly diverse country in terms of religion, belief, ethnic, race, language, culture, custom and tradition. As far as the religious diversity is concerned, it is the most challenging one for all people, particularly relating to the question of how to build lasting harmony between religious communities in culturally and religiously plural countries. Due to this highest urgency, this paper tries to briefly investigate the inter-religious harmony in the historical perspective. It is based on historical facts that all religion, especially Islam teaches the followers to promote peace and tolerance and to develop to live in harmony with other religions. Islam in fact frees non-Muslims: Christian, Catholic, Hindu, Buddhist, and etc to practice their faith and belief. In addition, this paper also shortly outlines the MUI’s role in improving interfaith dialogue to create interreligious harmony in Indonesia today. Keywords: peaceful, negotiations, dialogue, religion